Evaluation of efficacy of priming dose of propofol in reducing induction dose requirements in patients undergoing elective surgeries under general anaesthesia - Thakare, Devendra W.; Desai, Urvi H.; Sharma, Kailash S. (International Journal of Research in Medical Sciences, 2016)
Background: Priming principle refers to administration of a subanaestheic dose of an agent prior to its actual anaesthetic dose. Propofol is an effective substitute to thiopentone for intravenous induction. The objectives of the study were to evaluate whether priming with propofol would reduce induction of dose, reduce the peri-intubation haemodynamic changes, influence the severity of side effects and influence recall phenomenon. Methods: Sixty patients of ASA Grade 1 and 2, between 18-55 years of age group, of both sexes, were selected on the basis of eligibility criteria and scheduled for elective surgery under general anaesthesia were divided into study and control groups of 30 patients each. The total dose of propofol including the priming (25% of total) dose of propofol, heart rate and blood pressure, baseline (before induction), immediately after intubation, 1 min, 3 min, 5 min after induction, SPO2 (% of oxygen saturation), recall phenomenon and other side effects post operatively were studied. Results: The demographic data were comparable for age, weight and sex in both the groups. Total patients were divided into two groups with 30 patients each. It was observed that total induction dose of propofol was significantly decreased in the study group 72.33±9.53mg compared to control group 115.83±9.00mg. Heart rate was better maintained in study group with minimal post-intubation response. The values of systolic, diastolic and mean blood pressure observed at 1 min after induction also showed significant decrease in control group compared to study group. Conclusions: Propofol produces smooth, rapid, pleasant and safe induction. Priming with propofol can be practiced due to its cost effectiveness and better haemodynamic profile and safety.